Labour moblity within Europe. Comparison of opportunities between Belgium and Lithuania - Tonkūnaitė, Agnė (Socialinė teorija, empirija, politika ir praktika, 2006)
The purpose of this paper is to explore and analyse the situation of labour mobility in the European Union - how Belgium and Lithuania deal with and promote the right of free movement of workers in the EU. The review of migration policy in Europe and specifically in Belgium and Lithuania is presented in the first part of the paper. The research is presented in the second part of the paper. The purpose of this research is to find out and compare the experiences of Belgian and Lithuanian people who were working or are working in another European country than their own. The qualitative research approach and semi-structured interviews were used in this study. The clear list of issues and questions were prepared to interview both Belgian and Lithuanian people who were working or are working in another European country. The interviews conducted with both Belgian and Lithuanian citizens, working (high) skilled work (projects managers, project coordinators, doctors, scientists) reveal their migration purposes and advantages of living and working in a foreign country.